ENHANCED AEOLIAN ACTIVITIES IN THE MIDDLE YANGTZE RIVER BASIN DURING MIS2: EVIDENCE FROM RADIOCARBON DATING OF SAND HILLS AND LOESS SEDIMENTS. Issue 5 (9th October 2020) - Zhang, Zhi; Jia, Yulian; Wang, Yeqiao
ABSTRACT: Aeolian deposits are widely distributed in the middle Yangtze River Basin (YRB), central China. The formation of those aeolian deposits (including aeolian sands and loess deposits) represented the deterioration of local environment. Previous geochronological studies have shown that both aeolian sands and loess began to be deposited in the last interglacial (~100 ka). In this study, a total of four and six accelerator mass spectrometry radiocarbon (AMS 14 C) samples were collected from a sand hill and a loess section, respectively, in the Jiujiang area to refine their chronology. Charcoals extracted from bulk samples were employed for AMS 14 C dating. The sand layer at the lower part of the HG-C section is sandwiched by two mud layers dated to 26, 670–26, 285 and 24, 480–24, 180 cal BP, respectively. Therefore, we infer that aeolian activities in this region started at ~25 ka BP, which was significantly younger than that of previous studies. Meanwhile, thick loess began to deposit leeward of the sand hills in this region. Based on the AMS 14 C chronology and provenance tracing, we conclude that the loess was essentially the fine-grained aeolian deposits. Our results suggest that topography and vegetation cover have an important effect on the spatial distribution of aeolian deposits in this region.